Age polyethism in the swarm-founding wasp Metapolybia miltoni (Andena & Carpenter) (Hymenoptera: Vespidae; Polistinae, Epiponini) - Laura Chavarría; Fernando Barbosa Noll (Sociobiology)
Division of labor in Epiponini is associated with age polyethism and individual task specialization. We observed worker activities in three colonies of Metapoybia miltoni in Brazil. We analyzed differences of task allocation between age groups. Old workers tend to forage more than young, but age polyethism was less evident in other tasks. Age composition of population could be a determinant factor in task allocation. Possibly workers are allocate to perform tasks according to colony needs, and no to individual’s age. Consider age population in studies of division of labor could help to understand how colonies respond to different situations.